Narrative Review: Analysis of Nutritional Intake on The Quality of Students Learning Concentration - Andi Muh Ashar; Zulnadila Zulnadila2; Dina Agustina; Aji Septiana Rahmansyah; Dikdik Najmu Ramadan (Universitas Cahaya Prima, 2025)
Nutritional intake plays a vital role in supporting cognitive processes, particularly learning concentration among school-aged children. This narrative review examines the relationship between nutritional intake, learning concentration, and academic achievement. A systematic search through Google Scholar, PubMed, and Scimago identified 56 articles published between 2015 and 2024, of which nine met the inclusion criteria. The selected studies were analyzed thematically based on nutritional status, energy and protein adequacy, and the effects of nutrition education. The findings show that daily nutritional intake especially adequate energy and protein consumption and regular breakfast habits has a more direct and consistent influence on learning concentration than anthropometric nutritional status. Energy adequacy contributed 36.2% to concentration levels, and nutrition education significantly improved students’ energy and protein intake (p = 0.005). In contrast, several studies reported no significant association between nutritional status and academic achievement, indicating that concentration depends more on immediate nutrient availability than long-term health indicators. This review concludes that adequate nutritional intake is essential for sustaining attention and improving students’ learning outcomes. Schools should implement structured nutrition education, promote regular breakfast consumption, and support access to balanced meals. Future research should explore interactions between nutrition, sleep, physical activity, and socioeconomic factors to better understand the multifactorial determinants of concentration.